Analisis Kualitas Anggaran Pendapatan Dan Belanja Daerah Kabupaten Mimika Tahun 2018-2021 - Yundy Hafizrianda; Ida Ayu Purba Riani; Agustinus Salle (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2022)
This study aims to: (1) measure and analyze the performance of APBD management in Mimika Regency; (2) evaluate and analyze the quality of the Mimika Regency APBD; and (3) formulate recommendations for better quality APBD management policies in the future that can provide impetus for the acceleration of Mimika Regency's socio-economic development. The approach used in this study is a quantitative approach, in which the APBD quality assessment refers to eight APBD performance indicators measured using an ordinal scale and a composite index to obtain a value for the quality of APBD management in a given year. The results of data processing show that in 2018, the quality value of the Mimika Regency APBD only reached 72.92 points, which was included in the "less quality" category. Then in 2019, there was an increase in the quality of the Mimika Regency APBD with a value of 79.17 points, which was in the "sufficient quality" category. Likewise, for 2020, even though there was a decrease in the quality score compared to the previous year, it was still in the "sufficient quality" category with a quality score of 77.08 points. For the results of the 2021 assessment, there was a decrease compared to 2020, with an APBD quality score of 75.00 points, which caused the quality category to fall back to "less quality." Overall, the quality of the Mimika Regency APBD during 2018–2021 is indicated to be not yet satisfactory, which is most dominant due to the late determination of the APBD, the low level of fiscal independence, the non-fulfillment of the allocation of capital expenditures and education expenditures according to regulations, and the regional expenditures that have not been effective in accelerating economic growth and poverty reduction. Key Words : APBD Performance Indicator, Composite Index, APBD Quality